Implementasi Senam Yoga Ibu Hamil Trimester II dan III Sebagai Upaya Menyiapkan Persalinan Yang Aman di Kelas Hamil Desa Pliken - Melinda Agustin; Siti Haniyah; Ns. Noor Yunida Triana (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Pregnancy in the second and third trimesters is often accompanied by physical and psychological complaints such as back pain, difficulty sleeping, and anxiety about childbirth. One non-pharmacological method that can help reduce these complaints is yoga. However, a preliminary survey in Pliken Village showed that most pregnant women did not have sufficient knowledge about yoga and had never received any education on the subject. The objective of this Community Service activity is to enhance the knowledge and skills of pregnant women in the second and third trimesters through education and hands-on yoga practice as part of preparing for a safe and comfortable childbirth. The methods used include education through lectures, leaflets, and visual media, as well as guided yoga practice led by practitioners. Evaluation was conducted using pre-test, post-test, and yoga exercise SOP checklist instruments. The number of participants was 24 pregnant women. The results showed a significant improvement, where before education, 88% of participants were in the adequate knowledge category, while after education, 83% of participants were in the good knowledge category. Most participants were also able to practice yoga independently and showed enthusiasm in participating in the activities. In conclusion, education and yoga practice have been proven to improve the knowledge and skills of pregnant women in the second and third trimesters. This activity can be integrated into the routine program of prenatal classes as a promotive and preventive effort in preparing for a healthy and safe delivery. The outcomes of this Community Service Program include Intellectual Property Rights (IPR) and journal publications on Community Service.